THE IMPLEMENTATION OF LEARNING ENGLISH VOCABULARY THROUGH ASYNCHRONOUS CLASS - Pradana, Galih Rayi; Suryaman, Maman (PROJECT (Professional Journal of English Education), 2021)
Online Learning certainly has challenges for students and teachers in carrying out English learning activities. This activity is carried out through asynchronous classes due to the limitations of students' devices on each cellphone. When conducting asynchronous classes for the students studying English, social media can make students motivated to learn because of the openness in learning. This study aims to motivate the students to be more enthusiastic in learning English in appropriating Youtube and WhatsApp in the implementation of which does not promote social media. Employing the descriptive qualitative method, this activity can determine the percentage of their ability and experience in studying vocabulary in English as a Foreign method during a pandemic. It is found that this activity received a positive response but there were shortcomings due to having objections in downloading learning files on social media and experiencing signal difficulties. Moreover, they get waivers where the students can ask their problems from what they did to the teacher freely. It seems that the students who learn through social media can find new knowledge which should be extra and openly guided by the teacher during online learning.Â Keywords:Â  Asynchronous, Vocabulary, English, Youtube, WhatsApp